The relevance to medical science of doctors’ self-challenge experiments with pathogens or infectious agents: 1767-2022 - Brabin , Bernard; Brabin, Loretta (Medicina Historica, 2024)
Self-experimentation by medical doctors was a well-recognized research practice during the 18th and 19th centuries. This paper explores its contribution to the development of medical and public health practices by comprehensively collating, chronologically and by pathogenic group, reports of self-experimentation with infectious material and pathogens between the years 1767 and 2022. Tabulation of these events, which focuses primarily on physicians, provides a basis for understanding how the purpose of self-experimentation changed as medical knowledge developed. Reports are tabulated by year of experiment, country, investigator, experimental method, and clinical outcome. 43 self-challenge studies were conducted pre-1874 before proof of the germ theory of disease was accepted, mainly to investigate contagion. Results were often conflicting and anti-contagion views hindered acceptance of quarantine measures for yellow fever, cholera, and plague. Post-1874, 140 self-experiments took place, 17 with different parasites, 27 with different bacterial pathogens, and nine with different viruses or infectious agents, with peak frequency between 1891-1900. When specific agents of disease were known, anti-contagion theory was challenged, and experimental evidence used to explain clinical and disease patterns. Early study designs were limited as host immunity was not well understood. The reasons for putting oneself at great risk varied, although doctors were expected to set an example. Gradually their personal involvement declined in favour of consented volunteers, and reliance on a sample size of one became unacceptable.